Uniform Synthesis of Bilayer Hydrogen Substituted Graphdiyne for Flexible Piezoresistive Applications - Josline, Mukkath Joseph; Ghods, Soheil; Kosame, Saikiran; Choi, Jun Hui; Kim, Woongchan; Kim, Sein; Chang, Soo Hyun; Hyun, Sang Hwa; Kim, Seung Il; Moon, Ji Yun; Park, Hyeong Gi; Cho, Sung Beom; et al. (Small, 2024)
Graphdiyne (GDY) has garnered significant attention as a cutting-edge 2D material owing to its distinctive electronic, optoelectronic, and mechanical properties, including high mobility, direct bandgap, and remarkable flexibility. One of the key challenges hindering the implementation of this material in flexible applications is its large area and uniform synthesis. The facile growth of centimeter-scale bilayer hydrogen substituted graphdiyne (Bi-HsGDY) on germanium (Ge) substrate is achieved using a low-temperature chemical vapor deposition (CVD) method. This material's field effect transistors (FET) showcase a high carrier mobility of 52.6 cm2 V−1 s−1 and an exceptionally low contact resistance of 10 Ω µm. By transferring the as-grown Bi-HsGDY onto a flexible substrate, a long-distance piezoresistive strain sensor is demonstrated, which exhibits a remarkable gauge factor of 43.34 with a fast response time of ≈275 ms. As a proof of concept, communication by means of Morse code is implemented using a Bi-HsGDY strain sensor. It is believed that these results are anticipated to open new horizons in realizing Bi-HsGDY for innovative flexible device applications.
Keywords: Bi-layer; Chemical vapour deposition; Cutting edges; Graphdiyne; High mobility; Hydrogen substituted graphdiyne; Morse codes; Piezo-resistive; Strain sensors; Uniform growth; chemical vapor deposition; hydrogen substituted graphdiyne; morse code; strain sensors; uniform growth